1990
DOI: 10.1007/bf00226188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Escherichia coli lipopolysaccharide on phosphatidylcholine biosynthesis by rat lung and alveolar type II cells

Abstract: Alterations in pulmonary surfactant are partly responsible for the respiratory insufficiency seen under septic shock process. We have used an experimental model of LPS-induced shock in rats to examine the cells responsible for the pulmonary surfactant synthesis and its relationship to lung injury. (14C)Choline incorporation into phosphatidylcholine was significantly reduced in lung homogenates or type II cells obtained from LPS-treated animals. Addition of LPS in vitro fails to increase (14C)choline incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…One is that LPS induces a reduction in the synthesis of PC. In lung tissue it is reported that LPS induces a reduction in pulmonary surfactant (PC) synthesis [14,15]. However, we found no evidence to support this possibility in the stomach, as both of the primary biosynthetic pathways for PC synthesis in our hands were unaffected by LPS at the dose and times used (Table 2).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…One is that LPS induces a reduction in the synthesis of PC. In lung tissue it is reported that LPS induces a reduction in pulmonary surfactant (PC) synthesis [14,15]. However, we found no evidence to support this possibility in the stomach, as both of the primary biosynthetic pathways for PC synthesis in our hands were unaffected by LPS at the dose and times used (Table 2).…”
Section: Discussioncontrasting
confidence: 62%
“…Also, a possible role for gastric alkalinization in gastric injury was approached by use of the proton pump inhibitor omeprazole. Because LPS has been implicated in causing inhibition of PC synthesis in another system, i.e., lung [14,15], we further investigated the de novo synthesis of PC in the stomach and the effect on it of LPS. Finally, we tested by surgical manipulation (pylorus ligation) the importance of duodenogastric reflux of intestinal contents on PC levels altered by LPS.…”
Section: Introductionmentioning
confidence: 99%
“…Part of our studies have been focussed on the interaction of LPS (from E. coli 0111:B4) with isolated rat type I1 pneumocytes, whose metabolism, in particular the biosynthesis of phospholipids, is disrupted in endotoxemic rats and also by treatment of cells with LPS in vitro (Aracil et al, 1985: Bosch et al, 1990. For studying the distribution of the endotoxin at different times of treatment, immunogold labeling was performed on Lowicryl K4M sections of isolated pneumocytes incubated with LPS at 37°C during 15,25,40,60, 90, and 120 min.…”
Section: Visualization Of the Endotoxin Interaction With Target Cellsmentioning
confidence: 99%
“…(Modified from Risco et al, 1993a, with permission of Journal ofEZectron Microscopy, Center for Academic Publications Japan.) important is the impairment of the metabolic routes of type I1 pneumocytes that are probably unable to replace the surfactant lost (Bosch et al, 1990). Studies performed in vivo showed that endotoxins reach the alveolar regions and accumulate in alveolar macro-phages, also entering the endothelial and epithelial cells (Freudenberg et al, 1984).…”
Section: Visualization Of the Endotoxin Interaction With Target Cellsmentioning
confidence: 99%
“…The microcirculatory disturbances with subsequent cellular injury and loss of organ function induced by LPS in intact animals have been attributed to the activation of inflammatory cells and strong inflammatory mediator generation. ATII exposed to LPS demonstrated a marked depression of surfactant synthesis and ion transport as well as strong up-regulation of adhesion molecules, cytokines such as TNF-␣, and NO synthesis via NO synthase II (NOSII) (11)(12)(13)(14).…”
mentioning
confidence: 99%